Proceedings of the Fifteenth Workshop on Innovative Use of NLP for Building Educational Applications 2020
DOI: 10.18653/v1/2020.bea-1.12
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Natural Language Processing in Bilingual Language Teaching: An Indonesian-English Case Study

Abstract: Multilingual corpora are difficult to compile and a classroom setting adds pedagogy to the mix of factors which make this data so rich and problematic to classify. In this paper, we set out methodological considerations of using automated speech recognition to build a corpus of teacher speech in an Indonesian language classroom. Our preliminary results (64% word error rate) suggest these tools have the potential to speed data collection in this context. We provide practical examples of our data structure, deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The third model was trained with Indonesian data only. Our preliminary result of 64% word error rate (WER) is high in comparison to mono-lingual ASR systems (Maxwelll-Smith et al, 2020). However, WERs from code-switch bilingual data (Biswas et al, 2019) were more similar to our WER, especially given our small amount of training data.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The third model was trained with Indonesian data only. Our preliminary result of 64% word error rate (WER) is high in comparison to mono-lingual ASR systems (Maxwelll-Smith et al, 2020). However, WERs from code-switch bilingual data (Biswas et al, 2019) were more similar to our WER, especially given our small amount of training data.…”
supporting
confidence: 52%
“…Using quantitative methods to understand language learning and teaching is difficult work as the 'transcription bottleneck' constrains the size of datasets. We found that using an automatic speech recognition (ASR) toolkit with a small set of training data is likely to speed data collection in this context (Maxwelll-Smith et al, 2020).…”
mentioning
confidence: 99%
“…This work also contributes to the development and scrutiny of Indonesian NLP resources (Nomoto, 2020) which require significant investment given the population of Indonesian exceeds 270 million (WorldBank, 2019). It shows how using the same computational tools regularly used in industry can be helpful to advance the education sector (Maxwell-Smith et al, 2020), even for languages with scarce resources.…”
Section: Discussionmentioning
confidence: 96%
“…Another field reaping the benefits of advancements in NLP is voice-based applications that have been deployed in the form of voice-controlled devices [42], teaching and answering [43] and [44], customer service agents [45], voice and multimedia mining [46], and virtual assistants [47][48][49]. Sentiment analysis has also become a popular tool on the internet to assess the feedback and the emotions or context of text written by humans.…”
Section: The Advancements Made In Nlpmentioning
confidence: 99%